Tiktok as a Learning Media for Improving The Students’ Speaking Skills - Andi Kusumah, Rendi; Arltri Firdaus, Yudha; Muhammad Irham, Farhan (Journal of English Education and Teacher Trainer, 2025)
This study reports students' speaking ability through the use of TikTok application. The problem of this study is to improve speaking activity, fluency in speech and ability to convey diverse vocabulary through the use of TikTok application at SD Laboratory UPI Cibiru. The aim of this study was to determine students' speaking skills through the use of TikTok application. This research used Classroom Action Research (CAR) which is carried out in two cycles. Each cycle consisted of four meetings. Twenty-one sixth grade students of SD Laboratory UPI participated in this study. Data collection techniques were observation and speaking test. The findings of this study showed that the use of TikTok application significantly improved students' speaking skills in terms of speaking activeness, fluency of speech and ability to convey diverse vocabularies. This is evidenced in the pre-cycle, students who scored above the standard were 11 students with an average score of 66.90 and a percentage of 52.38%. At the cycle 1 stage, students who got the standard score were 16 students with an average score of 73.33 and a percentage of 76.19%. While in cycle 2, there were 20 students who got the standard score with an average score of 81.42 and a percentage of 95.23%.